Metabolic Changes in Focal Brain Ischemia in Rats Treated With Human Induced Pluripotent Stem Cell-Derived Neural Precursors Confirm the Beneficial Effect of Transplanted Cells - Jirak, Daniel; Ziolkowska, Natalia; Turnovcova, Karolina; Karova, Kristyna; Sykova, Eva; Jendelova, Pavla; Romanyuk, Nataliya (Frontiers in Neurology, 2019)
There is currently no treatment for restoring lost neurological function after stroke. A growing number of studies have highlighted the potential of stem cells. However, the mechanisms underlying their beneficial effect have yet to be explored in sufficient detail. In this study, we transplanted human induced pluripotent stem cell-derived neural precursors (iPSC-NPs) in rat temporary middle cerebral artery occlusion (MCAO) model. Using magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS) we monitored the effect of cells and assessed lesion volume and metabolite changes in the brain. We monitored concentration changes of myo-inositol (Ins), Taurine (Tau), Glycerophosphocholine+Phosphocholine (GPC+PCh), N-acetyl-aspartate+N-acetyl-aspartyl-glutamate (NAA+NAAG), Creatine+Phosphocreatine (Cr+PCr) and Glutamate+Glutamine (Glu+Gln) in the brains of control and iPSC-NP-transplanted rats. Based on initial lesion size, animals were divided into small lesion and big lesion groups. In the small lesion control group (SCL), lesion size after 4 months was three times smaller than initial measurements. In the small lesion iPSC-NP-treated group, lesion volume decreased after 1 month and then increased after 4 months. Higher concentrations of Cr+PCr metabolites were found in the SCL group 4 months after MCAO. Although animals with small lesions significantly improved their motor skills after iPSC-NP transplantation, animals with big lesions showed no improvement. However, our MRI data demonstrate that in the big lesion iPSC-NP-treated (BTL) group, lesion size increased only up until 1 month after MCAO induction and then decreased. In contrast, in the big lesion control group, lesion size increased throughout the whole experiment. Significantly higher concentrations of Ins, Tau, GPC+PCh, NAA+NAAG, Cr+PCr and Glu+Gln were found in in contralateral hemisphere in BTL animals 4 months after cell injection. Lesion volume decreased at this time point. Spectroscopic results of metabolite concentrations in lesion correlated with volumetric measurements of lesion, with the highest negative correlation observed for NAA+NAAG. Altogether, our results suggest that iPSC-NP transplantation decreases lesion volume and regulates metabolite concentrations within the normal range expected of healthy tissue. Further research into the ability of iPSC-NPs to differentiate into tissue-specific neurons and its effect on the long-term restoration of lesioned tissue is necessary.